Production of Advanced Materials by Methods of Self-Propagating High-Temperature Synthesis - Tavadze, Giorgi F.; Shteinberg, Alexander S.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This translation from the original Russian book outlines the production of a variety of materials by methods of self-propagating high-temperature synthesis (SHS). The types of materials discussed include: hard, refractory, corrosion and wear-resistant materials, as well as other advanced and speciality materials. The authors address the issue of optimal parameters for SHS reactions occurring during processes involving a preliminary metallothermic reduction stage, and they calculate this using thermodynamic approaches. In order to confirm the effectiveness of this approach, the authors describe experiments focussing on the synthesis of elemental crysalline boron, boron carbides and nitrides. Other parts of this brief include theoretical and experimental results on single-stage production of hard alloys on the basis of titanium and zirconium borides, as well as macrokinetics of degassing and compaciton of SHS-products.This brief is suitable for academics, as well as those working in industrial manufacturing companies producing hard alloys and composites for making metal-working machinery or drilling equipment.
Synthesis of elemental boron and its refractory compounds by self-propagating high-temperature synthesis with metallothermic reduction -- Hard titanium and zirconium boride alloys and items manufactured from them by SHS-compaction -- Production and analysis of TiB2-based hard alloys -- Macrokinetics of degassing during SHS -- Macrokinetics of SHS compaction.
Keywords: Chemistry, inorganic; Chemical engineering; Machinery; Materials; Materials Science; Structural Materials; Industrial Chemistry/Chemical Engineering; Inorganic Chemistry; Manufacturing, Machines, Tools